Psychological & linguistic approaches to language acquisition - Plunkett, Kim (Psyke & Logos, 2022)
Language acquisition research experienced a boom following the Chomskyian revolution. The focus of attention centred primarily on the English child's acquisition of syntax. In the seventies, the range of problem areas in language acquisition began to diversify and alternative perspectives (non-nativist) on how the child acquires language began to emerge. It is argued that socio-cognitive approaches to language acquisition, though providing an important prerequisite for the acquisition of linguistic structure, cannot themselves account for the acquisition of the complex mapping relation between grammar and meaning that is required for full-blooded linguistic communication. Recent trends in language acquisition research including Learnability theory, Individual differences and Cross-linguistic approaches are reviewed. The article concludes with speculation about the future role of non-nativist approaches in language acquisition research. Although much current detailed work would seem to point to the existence of a Language Acquisition Device that is specifically tuned to the processing of linguistic information, it is premature to conclude that amore general cognitive learning mechanism that is able to account for both universal and particular properties of linguistic development, cannot provide a more parsimonious explanation of acquisition.